Increased white matter connectivity seen in young judo athletes with MRI. Issue 10 (October 2018) - Toh, Z.H.; Gu, Q.L.; Seah, T.A.C.; Wong, W.H.; McNab, J.A.; Chuang, K.; Hong, X.; Tang, P.H.
Abstract : Aim: To compare the structural and functional differences in the brains of children who practise judo against controls using diffusion tensor imaging (DTI). Materials and methods: This prospective study was approved by the Institutional Review Board. Young judo athletes ( n =14; 17–21 years; mean, 19 years) and age-matched healthy controls ( n =7; 16–21 years; mean, 19 years) underwent standard structural brain magnetic resonance imaging (MRI) and DTI using a 3 T MRI system. Brain MRI images were reviewed for evidence of injury or structural anomalies. Tractography and the fractional anisotropy (FA) of white matter tracts were calculated. Between groups comparison was conducted using two-sample t -test. Results: The brains of the young judo athletes were structurally normal. Significantly increased FA, up to 18% in the internal capsule ( p <0.001), 22% in the genu of corpus callosum ( p <0.001), 13% in the trunk of corpus callosum ( p <0.005), 16% in the splenium of corpus callosum ( p <0.02) and 16% in the superior longitudinal fasciculus ( p =0.001), were found in the judo athletes compared to controls. Conclusion: DTI demonstrates that children who participate in judo have generalised increased FA compared to children with a less physically active lifestyle. Highlights: Young judo athletes show generalised increased white matter connectivity compared to those less physically active. The FA value measured is up to 22% higher in judo athletes. No evidence of trauma is seen in the brains of judo athletes who train in a safe environment under supervision.